Chemical Composition of the Essential Oil of Eucalyptus procera Dehnh. and Its Insecticidal Effects Against Two Stored Product Insects. Issue 5 (3rd July 2016) - Nouri-Ganbalani, Gadir; Ebadollahi, Asgar; Nouri, Alireza
Abstract: Botanical essential oils have been successfully used in controlling insect pests. In the present study, insecticidal activity of essential oil extracted from the leaves of messmate stringybark [ Eucalyptus procera Dehnh. (Myrtales: Myrtaceae)] were investigated through contact and fumigant toxicity against the cowpea weevil [ Callosobruchus maculatus (F.) (Coleoptera: Bruchidae)] and the red flour beetle [ Tribolium castaneum Herbst (Coleoptera: Tenebrionidae)]. Chemical analysis of the essential oil by Gas chromatography-Mass spectrometry proved 1, 8-cineole (45.0 %), α-pinene (28.6 %) and viridiflorol (5.7 %) were major constituents of the oil. The essential oil comprises 98.3 % terpenic compound including 31.4 % monoterpene hydrocarbons, 55.8 % oxygenated monoterpenes, 2.2 % sesquiterpene hydrocarbons and 8.9 % oxygenated sesquiterpenes. Results showed that C. maculatus and T. castaneum were very susceptible to the essential oil of E. procera in both contact and fumigant bioassays. 24 h-LC values were 0.124 and 0.129 μl/ cm2 in the contact toxicity and 11.722 and 13.9 μl/l air in the fumigant toxicity for C. maculatus and T. castaneum, respectively. LT50 values were 16.137 h for T . castaneum and 13.644 h for C. maculatus at the highest tested concentrations (24 μl/l air for T. castaneum and 20 μl/l air for C. maculatus ). Results of present study indicated that the essential oil of E. procera can be considered as anatural resource for C. maculatus and T. castaneum management.